2006
DOI: 10.1177/0885328206058786
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Crystallinity and Crystal Structure of Hylamer™ Polyethylene after in vivo Wear

Abstract: ABSTRACT:Hylamer TM polyethylene is a crystalline form of polyethylene of 70% crystallinity whereas conventional polyethylene (PE) has 50% crystallinity. Crystallinity is the percentage by weight of the crystalline phase present in the whole polymer, which comprises both amorphous and crystalline phases.Clinical experience has shown that Hylamer TM components used in joint prostheses, if sterilized by gamma rays in the presence of oxygen, are easily affected by wear, which leads to osteolysis. The authors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…The wear debris of this material produces a negative biological response, resulting in osteolysis and loosening of the implant [4,5]. Many researchers have attempted to improve the wear resistance and mechanical properties of UHMWPE through crosslinking [6][7][8], increasing crystallinity [9][10][11][12], and incorporating fillers [13][14][15][16][17][18][19][20][21][22][23]. Although crosslinking has improved wear rates dramatically in vitro, in vivo case studies show contrasting results, with an increase in crosslinking density resulting in reduced crack propagation resistance [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wear debris of this material produces a negative biological response, resulting in osteolysis and loosening of the implant [4,5]. Many researchers have attempted to improve the wear resistance and mechanical properties of UHMWPE through crosslinking [6][7][8], increasing crystallinity [9][10][11][12], and incorporating fillers [13][14][15][16][17][18][19][20][21][22][23]. Although crosslinking has improved wear rates dramatically in vitro, in vivo case studies show contrasting results, with an increase in crosslinking density resulting in reduced crack propagation resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the size and number of wear debris particles produced from highly cross-linked UHMWPE may have more of an influence on the development of osteolysis than the wear debris of conventional UHMWPE [8]. Similarly, highly crystalline UHMWPE processed by exceedingly high pressure has shown poor properties in vivo, attributed to a change in the crystal structure of UHMWPE [12]. Because of the unsatisfactory results in vivo for cross-linked and highly crystalline UHMWPE, then it is worthwhile to investigate alternative methods of improving UHMWPE properties through the incorporation fillers.…”
Section: Introductionmentioning
confidence: 99%
“…The CH 2 twist vibration of PE is represented by the 1300 cm −1 peak. Finally, a triplet spanning 1420 to 1500 cm −1 is related to CH 2 bending vibration [23,24]. Next, Raman spectra of sulfonated PE sample was examined.…”
Section: Resultsmentioning
confidence: 99%
“…In order to better understand the crystallization behaviour of PE under the RC process, Raman spectroscopy was used to study the regions of the rigid amorphous fraction. Although the structure of rigid amorphous phase is still not clear, Raman has been found to be a useful direct method to detect the third, intermediate state of order, and Strobl and Hagedorn have reported that the mass fractions of intermediate state of PE samples could be derived directly from the integral intensities of characteristic Raman bands without any additional calibration procedure 36,47,48 . Figure 7 shows the recorded Raman spectra in the region of 1000-1600 cm -1 corresponding to the spectra commonly observed for semicrystalline PE, then the measured Raman spectra were deconvoluted into individual bands using Gauss functions, and an approximation of the measured spectra from these Gauss deconvolutions is shown.…”
Section: Crystallite Size and The Rigid Amorphous Partmentioning
confidence: 99%